The concept of real estate in civil law, its state registration and cancellation of state registration (Diversity Research: Journal of Analysis and Trends, 2024)
In this article, a general understanding of real estate objects, their signs, theories of scientists about it, the correct application of norms related to real estate objects in civil law, the representation of real estate objects in foreign legislation, the sequence of state registration of real estate, cancellation of state registration and opinions about real estate are widely expressed.